A Representasi Pluralitas Agama dalam Film - Pram Aditya Gamaputra (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2022)
A film that is presented or made can describe a reality of life that is faced now, or is a picture that will happen in the future. Films that depict events or something that will be achieved in the future, such as futuristic films or science fiction that we may have watched such as Star Trek, technologies in the Avanger film, Real Steel, and several anime films such as Doraemon, Gundam, and many other films. Meanwhile, films that describe current events or something that has actually happened, such as biographical films, war films, even light films that tell or reflect something real that humans often or can experience at this time. Based on observations, the film